The Validity of Self-Reported Medication Adherence as an Outcome in Clinical Trials of Adherence-Promotion Interventions: Findings from the MACH14 Study - Simoni, Jane M. (AIDS Behav, 2014)
In medication adherence-promotion trials, participants in the intervention arm are often cognizant of the researcher’s aim to improve adherence; this may lead to their inflating reports of their own adherence compared to control arm participants. Using data from 1,247 HIV-positive participants across eight U.S. Studies in the Multisite Adherence Collaboration on HIV (MACH14) collaboration, we evaluated the validity of self-reported adherence by examining whether its association with two more objective outcomes [1], electronically monitored adherence and [2] viral load, varied by study arm. After adjusting for potential confounders, there was no evidence of greater overestimation of self-reported adherence among intervention arm participants, supporting its potential as a trial outcome indicator.